The genetic associations of COVID-19 on genitourinary symptoms - Chang, Zhenglin; An, Lingyue; Lei, Min; Song, Zhenfeng; Deng, Jian; Tang, Ruizheng; Cheng, Zhangkai J.; Wu, Wenqi; Sun, Baoqing (Frontiers in Immunology, 2023)
Background: Recently emerged reports indicated that patients with coronavirus disease 2019 (COVID-19) might experience novo genitourinary symptoms after discharge. Nevertheless, the causal associations and underlying mechanisms remain largely unclear. Methods: Genome-wide association study (GWAS) statistics for COVID-19 and 28 genitourinary symptoms with consistent definitions were collected from the COVID‐19 Host Genetic Initiative, FinnGen, and UK Biobanks. Mendelian randomization (MR) analyses were applied to explore the causal effects of COVID-19 on genitourinary disorders by selecting single-nucleotide polymorphisms as instrumental variables. Meta-analyses were conducted to evaluate the combined causal effect. Molecular pathways connecting COVID-19 and its associated disorders were evaluated by WGCNA and enrichment analyses to extract insights into the potential mech¬¬¬¬anisms underlying the connection. Results: The MR and meta-analyses indicated that COVID-19 was causally associated with increased risk for calculus of the lower urinary tract (LUTC, OR: 1.2984 per doubling in odds of COVID‐19, 95% CI: 1.0752–1.5680, p = 0.007) and sexual dysfunction (SD, OR: 1.0931, 95% CI: 1.0292–1.1610, p = 0.004). Intriguingly, COVID-19 might exert a slight causal protective effect on the progression of urinary tract infections (UTIs) and bladder cancer (BLCA). These results were robust to sensitivity analyses. Bioinformatic analyses indicated that the inﬂammatory-immune response module may mediate the links between COVID‐19 and its associated disorders at the molecular level. Conclusions: In response to post-COVID-19 symptoms, we recommend that COVID-19 patients should strengthen the prevention of LUTC and the monitoring of sexual function. Meanwhile, the positive effects of COVID-19 on UTIs and BLCA should attach equal importance.